UJI POTENSIODINAMIK MATERIAL PELAPIS ANTI- KOROSI: Acrylic Paint-PANi/SiO2 - Munasir Munasir; H Umah; D M T Syahra (JPSE (Journal of Physical Science and Engineering), 2016)
Polyaniline (PANi) was succesfully prepared from Ammonium Peroxodisulfate (APS) and anyline using chemical oxidation method. Silica (SiO2) was synthesized from natural sands taken from Banjar. PANi/SiO2 composites were prepared using mechanical mixing route. The composites were prepared by variating the weight compositions of PANi:SiO2 of 2.5%, and 5% for SiO2. Furthermore, the coating process of Paint-PANi/SiO2 on SS304 stainless stell by spray coating technique. The characterization of anticorrosive behaviour of Paint-PANi/SiO2 was tested by potentiodynamics method. The obtained Tafel curve was then analyzed by means of ANOVA method. The best anticorrosive performance refered to the sample of Paint-PANi/(5%)SiO2, both of before and after exposure processes. The corrotion rate of before and after exposure processes were 0,00896000 mpy and 0,00024408, respectively. DOI: http://dx.doi.org/10.17977/um024v1i12016p025